AN ANALYSIS OF ARGUMENT STRUCTURE IN LANGUAGE TEACHING RESEARCH ARTICLE ON DISCUSSION PART PUBLISHED IN IJAL JOURNAL BASED ON TOULMIN ARGUMENT PATTERN ( TAP ) - Annisa Sofia Zikrillah; Ririn Putri Ananda (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Writing argumentative is an important skill for anyone in Education world, especially for anyone want to study further in English. In this case this related to every institution will usually publish nationally indexed journals as their benchmark in finding references, one of which is a research sample. The writing in this discussion is choosing objects related to